Limits and challenges of waste picker organizations: an analysis by ASMARE: an analysis by ASMARE - Rocha Sousa, Romário (2021)
The past decade has seen a significant increase in collective ventures of recyclable materials. In Belo Horizonte, ASMARE, seen as a pioneering experience, has become a reference in the articulation of new organizations. However, economic crises and governmental alternations impacted the organization. In this sense, the article aims to analyze ASMARE's trajectory, highlighting the limits and challenges faced in its historical process of struggles and resistance. In methodological terms, the qualitative approach adopted encompassed the performance of semi-structured interviews and Content Analysis to assess the data. The results showed that the Association faces a crisis that is not restricted to financial aspects since its implications resonate in the political formation of its members. Although the Brazilian recycling chain is recognized and admired, with the participation of several companies, associations, and cooperatives, it is often the entrepreneurs and middlemen who benefit most from a vicious cycle of exploitation of the precarious work of collectors. The struggle trajectory of ASMARE members represents an important milestone in the history of the waste pickers' movement in Brazil; however, it comes up against the constant challenge of sustaining collective actions in a society marked by inequality and exclusion.